LIPAD (LRRK2/Luebeck International Parkinson's Disease) Study Protocol: Deep Phenotyping of an International Genetic Cohort - Usnich, Tatiana; Vollstedt, Eva-Juliane; Schell, Nathalie; Skrahina, Volha; Bogdanovic, Xenia; Gaber, Hanaa; Förster, Toni M.; Heuer, Andreas; Koleva-Alazeh, Natalia; Csoti, Ilona; Basak, Ayse Nazli; Ertan, Sibel; et al. (Frontiers in Neurology, 2021)
Background. Pathogenic variants in the Leucine-rich repeat kinase 2 (LRRK2) gene are the most common known monogenic cause of Parkinson´s disease (PD). LRRK2-linked PD is clinically indistinguishable from idiopathic PD and inherited in an autosomal dominant fashion with reduced penetrance and variable expressivity that differ across ethnicities and geographic regions. Objective. To systematically assess clinical signs and symptoms including non-motor features, comorbidities, medication and environmental factors in PD patients, unaffected LRRK2 pathogenic variant carriers, and controls. A further focus is to enable the investigation of modifiers of penetrance and expressivity of LRRK2 pathogenic variants using genetic and environmental data. Methods. Eligible participants are invited for a personal or online examination which comprises completion of a detailed eCRF and collection of blood samples (to obtain DNA, RNA, serum/plasma, immune cells), urine as well as household dust. We plan to enroll 1,000 participants internationally: 300 with LRRK2-linked PD, 200 with LRRK2 pathogenic variants but without PD, 100 PD patients with pathogenic variants in the GBA or PRKN genes, 200 patients with idiopathic PD, and 200 healthy persons without pathogenic variants. Results. The eCRF consists of an investigator-rated (1 hour) and a self-rated (1.5 hours) part. The first part includes the Movement Disorder Society Unified Parkinson’s Disease Rating, Hoehn &Yahr and Schwab & England Scales, the Brief Smell Identification Test and Montreal Cognitive Assessment. The self-rating part consists of a PD risk factor, food frequency, autonomic dysfunction and quality of life questionnaires, the Pittsburgh Sleep Quality Inventory, and the Epworth Sleepiness as well as the Hospital Anxiety and Depression Scales. The first fifteen centers have been initiated and the first 150 participants enrolled (as of March 25th, 2021). Conclusions. LIPAD is a large-scale international scientific effort focusing on deep phenotyping of LRRK2-linked PD and healthy pathogenic variant carriers, including the comparison with additional relatively frequent genetic forms of PD, with a future perspective to identify genetic and environmental modifiers of penetrance and expressivity. Clinical Trial Registration. This study is registered on ClinicalTrials.gov (NCT04214509) since the 2nd of January 2020.